Lo efímero y la ciudad turística. A propósito de los haceres y lugares del turismo en el espacio urbano - Aragón, Milton (Diálogos Latinoamericanos, 2013)
The article explores the possibility of being tourists as the locals, and lives the everyday life of the locals in a city. The ephemeral plays an important role. The point of departure is the tourists their dreams embedded in the tourist places. The article analyses how the tourist sites operate.